2017
DOI: 10.1111/jorc.12198
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal function in a specific population of living kidney donors

Abstract: Kidney donation is unquestionably a safe procedure. However, a better understanding of the long-term consequences of living donor kidney transplantation is still needed. This knowledge may have important implications for the follow-up of these patients. Our study has demonstrated a non-negligible presence of an early marker of glomerular injury and a decrease in the GFR of some patients, thereby reinforcing the proposal for long-term follow-up of living kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Azar et al reported 86 donors over a period of 3 years post kidney transplantation and relayed high rates of hypertension (37.5%) and proteinuria (10.4%) despite strict control before kidney donation. In addition, De Souza Rodrigues analyzed 33 live donor patients, the majority female and hypertensive, and showed that many suffered long‐term side effects, such as early markers of glomerular injury and a decrease in GFR. In their report, the donors tended to be older and have higher incidence of hypertension.…”
Section: Discussionmentioning
confidence: 63%
“…Azar et al reported 86 donors over a period of 3 years post kidney transplantation and relayed high rates of hypertension (37.5%) and proteinuria (10.4%) despite strict control before kidney donation. In addition, De Souza Rodrigues analyzed 33 live donor patients, the majority female and hypertensive, and showed that many suffered long‐term side effects, such as early markers of glomerular injury and a decrease in GFR. In their report, the donors tended to be older and have higher incidence of hypertension.…”
Section: Discussionmentioning
confidence: 63%